Problematika Implementasi Kurikulum 2013 Pada Mata Pelajaran Pendidikan Agama Islam Dan Budi Pekerti Di Sekolah Menengah Atas (SMA) Antartika Sidoarjo - Millatus Shofi; Mei Kalimatusyaro (Program Studi Pendidikan Agama Islam, 2021)
The Problems of Implementing the 2013 Curriculum in the Subjects of Islamic Religious Education and Character at SMA Antartika Sidoarjo. This research methodology is a type of descriptive qualitative research. Descriptive research is research that is intended to collect information about the status of an existing symptom, namely the state of the symptoms according to what they were at the time the research was conducted. The implementation of the 2013 Curriculum in the subjects of Islamic Religious Education and Character at SMA Antarctica can be categorized as very good. the results showed that learning in class X IPA 6 for the first meeting gave a percentage of 90.47%, while for the second meeting the percentage was 92.06%. Learning in class X IPA 7 at the first meeting gave a percentage of 91.26%, while for the second meeting the percentage was 89.68%. Learning in class XI MIA Ef 1 for the first meeting gave a percentage of 84.12%, while for the second meeting the percentage was 88.88%. Learning in class XI MIA Ef 2 for the first meeting gave a percentage of 90.47%, while for the second meeting the percentage was 88.88%.